Green Tourism In Sustainable Tourism Development in Bali Based On Local Wisdom - Anak Agung Sagung Laksmi Dewi; Mella Ismelina Farma Rahayu; Anak Agung Ngurah Adhi Wibisana (Faculty of Law, Universitas Jenderal Soedirman, 2023)
Abstract The emergence of tourism as a major industry is one of the most remarkable changes that have occurred in global economic activity. Over the last three decades, issues related to the environment and sustainable development related to tourism, especially in Bali, have developed from a marginal topic into a focus of consideration and research. The purpose of this research is to find a novelty in the use of the concept of green tourism as a method that is seen as capable of supporting sustainable tourism development based on local wisdom, especially in Bali. The research used is normative legal research on Law no. 10 of 200b concerning Tourism with a statutory and conceptual approach. This study found that various statutory regulations, including Law no. 10 of 2009 concerning Tourism, namely through sustainable tourism all resources can be managed so as to meet needs and maintain cultural integrity, ecological dimension biodiversity, and system life.Keywords: Bali; Green Tourism; Sustainable Tourism; Local Wisdom.